Integration of network pharmacology and molecular docking to explore the molecular mechanism of Cordycepin in the treatment of Alzheimer’s disease - Ma, Xiaoying; Zhao, Ying; Yang, Tao; Gong, Na; Chen, Xun; Liu, Guoli; Xiao, Jun (Frontiers in Aging Neuroscience, 2022)
[Background] Cordycepin is a nucleoside adenosine analog and an active ingredient isolated from the liquid fermentation of Cordyceps. This study sought to explore the mechanism underlying the therapeutic effect of Cordycepin against Alzheimer's Disease using network pharmacology and molecular docking technology. [Methods] TCMSP, SYMMAP, CTD, Super-pred, SEA, GeneCards, DisGeNET database and STRING platform were used to screen and construct the target and protein interaction network of Cordycepin for Alzheimer's disease. The results of Gene Ontology annotation and KEGG pathway enrichment analysis were obtained based on the DAVID database. The Omicshare database was also applied in GO and KEGG pathway enrichment analysis of the key targets. The protein-protein interaction network was constructed using the STRING database, and the potential effective targets for AD were screened based on the degree values. The correlation between the potential targets of Cordycepin in the treatment of AD and APP, MAPT, and PSEN2 was analyzed using (GEPIA) databases. We obtained potential targets related to aging using the Aging Altas database. Molecular docking analysis was performed by AutoDock Vina and Pymol software. Finally, we validated the significant therapeutic targets in the Gene Expression Omnibus (GEO) database. [Results] A total of 74 potential targets of Cordycepin for treating Alzheimer's disease were identified. The potential targets of Cordycepin for the treatment of AD mainly focused on Lipid and atherosclerosis(hsa05417), Platinum drug resistance(hsa01524), Apoptosis(hsa04210) and Pathways in cancer(hsa05200). Our findings suggest that the therapeutic effect of Cordycepin on AD is primarily associated with these biological processes. We obtained 12 potential therapeutic targets for AD using the degree value in Cytoscape. Interestingly, AKT1, MAPK8, BCL2L1, FOXO3 and CTNNB1 were not only significantly associated with pathogenic genes (APP, MAPT and PSEN2) but also with longevity in Alzheimer's Disease. Thus we speculated that the five target genes were potential core targets mediating the therapeutic effect of Cordycepin against AD. Moreover, molecular docking results analysis showed good binding affinity between Cordycepin and the five core targets. Overall, MAPK8, FOXO3 and CTNNB1 may have significant clinical and treatment implications.